Contextual blending of ingroup/outgroup face stimuli and word valence: LPP modulation and convergence of measures - González Ramiro; Haye Andrés; Hurtado Esteban; Manes Facundo; Ibáñez Agustiń (BMC Neuroscience, 2009)
Abstract Background Several event related potential (ERP) studies have investigated the time course of different aspects of evaluative processing in social bias research. Various reports suggest that the late positive potential (LPP) is modulated by basic evaluative processes, and some reports suggest that in-/outgroup relative position affects ERP responses. In order to study possible LPP blending between facial race processing and semantic valence (positive or negative words), we recorded ERPs while indigenous and non-indigenous participants who were matched by age and gender performed an implicit association test (IAT). The task involved categorizing faces (ingroup and outgroup) and words (positive and negative). Since our paradigm implies an evaluative task with positive and negative valence association, a frontal distribution of LPPs similar to that found in previous reports was expected. At the same time, we predicted that LPP valence lateralization would be modulated not only by positive/negative associations but also by particular combinations of valence, face stimuli and participant relative position. Results Results showed that, during an IAT, indigenous participants with greater behavioral ingroup bias displayed a frontal LPP that was modulated in terms of complex contextual associations involving ethnic group and valence. The LPP was lateralized to the right for negative valence stimuli and to the left for positive valence stimuli. This valence lateralization was influenced by the combination of valence and membership type relevant to compatibility with prejudice toward a minority. Behavioral data from the IAT and an explicit attitudes questionnaire were used to clarify this finding and showed that ingroup bias plays an important role. Both ingroup favoritism and indigenous/non-indigenous differences were consistently present in the data. Conclusion Our results suggest that frontal LPP is elicited by contextual blending of evaluative judgments of in-/outgroup information and positive vs. negative valence association and confirm recent research relating in-/outgroup ERP modulation and frontal LPP. LPP modulation may cohere with implicit measures of attitudes. The convergence of measures that were observed supports the idea that racial and valence evaluations are strongly influenced by context. This result adds to a growing set of evidence concerning contextual sensitivity of different measures of prejudice.